Student Development Characteristics - Zakira; Bulan (International Journal of Students Education, 2024)
This study aims to describe the characteristics of students at an educational institution. This study uses a literature review. Data obtained from various references such as books and scientific articles are collected and analyzed related to students. This article tries to elaborate on the ability of teaching staff to understand the characteristics of students by optimizing the achievement of the learning process. At the implementation level, the success of the learning process is certainly related to the ability of teaching staff to understand students' subjects that have differences, both physical and non-physical dimensions. Therefore, it is necessary to study the developmental characteristics of elementary school students. The purpose of this writing is to provide information regarding the development of elementary school students. This article was created with the aim of providing readers with knowledge about the characteristics of students in order to maximize learning, namely by understanding each student's characteristics from various intelligences and learning styles. So that learning can run smoothly, namely by equalizing students' understanding of various characteristics. With smooth learning, the goals of the learning will be easily achieved and will benefit teachers and students. Besides that, student characteristics are related to several important elements such as intellectual, physical, emotional and moral aspects. It is important to note all these aspects that differences in era will determine differences in treatment. Differences in treatment are increasingly demanded along with changes and developments in technological science.